PERENCANAAN DAN ANALISIS KEBUTUHAN PENGGUNA DALAM PENGEMBANGAN SISTEM INFORMASI HUBUNGAN PELANGGAN - Putrianto, Novenda kartika; Widyastuti, Yuanita Maria; Oktiarso, Teguh (Universitas Ma Chung, 2024)
This study aims to plan and analyze the development of a Customer Relationship Management (CRM) system at PT XYZ, a company in the financial services sector. Facing increasing competition, PT XYZ requires a structured CRM system to enhance operational efficiency, customer relationship management, and support pemasaran and sales activities. This study employs the System Development Life Cycle (SDLC) approach, focusing on the initial two phases: planning and analysis. Data was collected through interviews, observations, and literature studies to formulate the vision and mission, as well as to identify the functional and non-functional requirements of the system. The results indicate that by establishing a clear vision and mission and comprehensively identifying user needs, the planned CRM system can effectively address the operational challenges of PT XYZ. The key features identified include contact management, complaint handling, knowledge support, and pemasaran campaign management. These findings provide a crucial foundation for progressing to the design and implementation phases, with the expectation of improving company performance and strengthening competitive advantage in the market. The study concludes that systematic planning and analysis are critical steps in the development of an effective information system.